The Occupation of Play - Bundy, Anita; Kuhaneck, Heather (The American Journal of Occupational Therapy, 2024)
The articles for the Special Section on Play highlight the complexity of play and the many ways occupational therapy practitioners study and promote play with children, families, and adults across individual, school, family, political, and cross-cultural settings. The authors of the articles in this issue view the importance of play across the lifespan and through multiple research lenses, including play preference, environmental supports for and barriers to play, the skills required to succeed in play, and the extent to which play is self-determined. The guest editors offer suggestions for how to enhance occupational therapy’s voice in the study and promotion of play as a primary lifelong occupation.
Keywords: dept.rec; peer-reviewed